2018
DOI: 10.3389/fnagi.2018.00366
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Alzheimer’s Disease Using Non-invasive Near-Infrared Spectroscopy

Abstract: Mild cognitive impairment (MCI) is a cognitive disorder characterized by memory impairment, wherein patients have an increased likelihood of developing Alzheimer’s disease (AD). The classification of MCI and different AD stages is therefore fundamental for understanding and treating the disease. This study aimed to comprehensively investigate the hemodynamic response patterns among various subject groups. Functional near-infrared spectroscopy (fNIRS) was employed to measure signals from the frontal and bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 56 publications
3
57
1
1
Order By: Relevance
“…In most of the reviewed applications, fNIRS probes were placed over the PFC, as this cortical area is mainly associated with high-level processing functions [64]. We identified 40 studies performed with a total of 977 AD and 477 MCI patients (208 amnestic MCI), as well as with 792 age-matched HC subjects (Table 2) Most studies were addressed to the monitoring of tissue oxygenation [65][66][67][68][69][70], the investigation of functional resting-state activity and connectivity [64,[71][72][73], the assessment of specific cognitive functions [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] such as visuospatial deficits [94,95] and additional ecological applications [96,97]. Though most studies reported cross-sectional reports, we also retrieved six longitudinal ones [98][99][100][101][102][103], thus strongly supporting the idea that fNIRS can represent a viable tool for long-term monitoring of cerebral activity from the early phases of the disease or during r...…”
Section: Fnirs In Alzheimer's Disease and Mild Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the reviewed applications, fNIRS probes were placed over the PFC, as this cortical area is mainly associated with high-level processing functions [64]. We identified 40 studies performed with a total of 977 AD and 477 MCI patients (208 amnestic MCI), as well as with 792 age-matched HC subjects (Table 2) Most studies were addressed to the monitoring of tissue oxygenation [65][66][67][68][69][70], the investigation of functional resting-state activity and connectivity [64,[71][72][73], the assessment of specific cognitive functions [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] such as visuospatial deficits [94,95] and additional ecological applications [96,97]. Though most studies reported cross-sectional reports, we also retrieved six longitudinal ones [98][99][100][101][102][103], thus strongly supporting the idea that fNIRS can represent a viable tool for long-term monitoring of cerebral activity from the early phases of the disease or during r...…”
Section: Fnirs In Alzheimer's Disease and Mild Cognitive Impairmentmentioning
confidence: 99%
“…However, the WM task performance and the averaged response were lower and delayed in the AD group compared to HCs, suggesting that the α4β2 nicotinic acetylcholine receptor system supports PFC activity associated with cognitive tasks. Recently, Li et al [91] investigated the hemodynamic response patterns of MCI and AD patients of different severity during a verbal digit span task. Lower HbO2 concentrations across frontal and bilateral parietal cortices were associated with the severity of the disease, while MMSE scores were significantly correlated with all fNIRS-derived hemodynamic indices.…”
Section: Cognitive Tasks-memory Taskmentioning
confidence: 99%
“…The mean and slope of the HbO responses were correlated with the clinical scores, and the scores of the MCI patients stayed below those of the mild and moderate-to-severe AD patients. 236…”
Section: Digit Span Taskmentioning
confidence: 99%
“…244 A time-series analysis revealed that the reduction or decline in HbO levels becomes steeper when the intensity of AD progresses. 236…”
Section: Digit Span Testmentioning
confidence: 99%
See 1 more Smart Citation